2016
DOI: 10.1111/eea.12451
|View full text |Cite
|
Sign up to set email alerts
|

Varroa treatment with bromfenvinphos markedly suppresses honeybee biochemical defence levels

Abstract: We examined the influence of bromfenvinphos, a commonly used acaricide, on activities of many metabolic enzymes affecting the biochemical defences/physiology of the western honeybee, Apis mellifera L. (Hymenoptera: Apidae), as well as on some metabolic compound concentrations, percentage of global DNA methylation, and Nosema spp. infection levels. Bromfenvinphos-treated workers had decreased haemolymph volumes and higher protein concentrations on their cuticle but lower protein concentrations in the haemolymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 57 publications
6
33
0
Order By: Relevance
“…This also suggested that honeybees can adapt to IMD through epigenetic mechanisms (Flores et al 2013;Dong et al 2013) or that at least the far-reaching IMD caused nonadaptive epigenetic changes occur. Similar epigenetic responses have already been observed in honeybees exposed to other harmful xenobiotics (Strachecka et al 2012b(Strachecka et al , 2016. On the other hand, the global DNA methylation level increased with honeybee age in the present study (Online Resource 2), which corresponds to the results of Lyko and Maleszka (2011) and Cardoso-Júnior et al (2018).…”
Section: Queenssupporting
confidence: 90%
See 2 more Smart Citations
“…This also suggested that honeybees can adapt to IMD through epigenetic mechanisms (Flores et al 2013;Dong et al 2013) or that at least the far-reaching IMD caused nonadaptive epigenetic changes occur. Similar epigenetic responses have already been observed in honeybees exposed to other harmful xenobiotics (Strachecka et al 2012b(Strachecka et al , 2016. On the other hand, the global DNA methylation level increased with honeybee age in the present study (Online Resource 2), which corresponds to the results of Lyko and Maleszka (2011) and Cardoso-Júnior et al (2018).…”
Section: Queenssupporting
confidence: 90%
“…Similar to pathogens and other xenobiotics (Bajda et al 2014;Strachecka et al 2015Strachecka et al , 2016, ALT, AST, and ALP were downregulated, independent of the caste and age, when bees were exposed to IMD (Table II). This confirmed our hypothesis 3 and pointed out the harmful, physiological side effects of IMD.…”
Section: Queensmentioning
confidence: 89%
See 1 more Smart Citation
“…Oxidative imbalance and decreased endogenous antioxidants lead to the release of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase enzymes (ALP) (Mehta et al, 2012). However, the mechanism of AST, ALP and ALT activation in bees is opposite to that in mammals (Bajda et al, 2014;Strachecka et al, 2014aStrachecka et al, , 2014bStrachecka et al, , 2016, as increased activities seem to be indicators of improved health and resistance (Łoś and Strachecka, 2018). In the current study, higher activities of these enzymatic biomarkers in the haemolymph of piperine-treated workers compared with untreated bees indicates a reduction of oxidative stress and support of the defence systems, similar to curcumin, caffeine, CoQ10 and vitamin C (Farjan et al, 2012;Strachecka et al, 2014aStrachecka et al, , 2014bStrachecka et al, , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was carried out on 8000 1-day-old worker bees (Apis mellifera carnica, Pollmann; collected from an apiary belonging to the University of Life Sciences in Lublin -51°1 3 ′ 31 ′′ N, 22°38 ′ 07 ′′ E), prepared according to the method of Strachecka et al (2016) in June and July 2017. Bees were settled into 200 wooden cages (40 bees/cage) with a volume of 576 cm 3 each (12 × 12 × 4 cm 3 , length/height/width), with a sliding front window, air vents located on the side and a feeder (a syringe with a modified adaptor) on the top.…”
Section: Methodsmentioning
confidence: 99%